OLD TERMIZ SPHEROCONICAL VESSELS (World Bulletin of Social Sciences, 2025)
Simobko‘zacha (Sphero-conical vessel) are one of the most distinctive pottery vessels with their unique shape. This article discusses the finds and their typology from Old Termez, one of the mercury jar production centers of Central Asia.